Validating the Parkinson’s Disease Questionnaire (PDQ-39) in the Arab context: a pilot study among Tunisian patients - Chiraz Azaiez; Nasr Chalghaf; Imane Ghalmi; Ghada Boussayala; Mohamed Houcine Ibrahim Alajjouri; Nabil Muttlak El-Sadoon; Ali Ibrahim Abdul Wahid Al-Saadi; Mazin Inhaier Lami; Amel ben Chida Jammoussi; Choukri ben Ayed; Ismail Dergaa; Fairouz Azaiez (Cogent Psychology, 2024)
Parkinson’s Disease (PD) is a progressive neurological disorder affecting patients’ quality of life (QoL). The Parkinson’s Disease Questionnaire (PDQ‑39) is a widely used instrument for assessing health‑related QoL in PD, but it has not been validated for Arabic‑speaking populations. This pilot study aims to validate the Arabic version of the PDQ‑39 in the Arab context, specifically among Tunisian patients. A total of 433 patients diagnosed with PD, recruited from four regional hospitals in Tunisia, were selected for the study. Eligible participants were those aged 50 years and older, diagnosed with PD for at least one year, and able to understand and complete the PDQ‑39 questionnaire. The questionnaire was administered through structured interviews conducted by trained healthcare professionals to ensure clarity and comprehension. We conducted both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to examine the factorial structure. Internal consistency was assessed using Cronbach’s alpha and McDonald’s omega. The EFA revealed eight factors with eigenvalues above 1, and the CFA demonstrated a good model fit (CFI = 1.12, RMSEA = 0.08). The PDQ‑39 showed strong internal consistency (α = 0.763 to 0.923) and good convergent and discriminant validity. Our findings support the use of the Arabic PDQ‑39 as a reliable tool for assessing QoL in Tunisian PD patients, with potential for broader application across Arabic‑speaking populations.